MWCNT Aided Cobalt Antimony Sulfide Electrocatalyst for Dye-Sensitized Solar Cells and Supercapacitors: Designing Integrated Photo-Powered Energy System. Issue 5 (1st May 2022) - Peter, I. John; Vijaya, S.; Anandan, S.; Karazhanov, Smagul; Nithiananthi, P.
Abstract : The objective of this study is to demonstrate low-cost Pt-free Dye-Sensitized Solar Cells (DSSCs) and an electrode for supercapacitor. Cobalt Antimony Sulfide (CoSbS) and Multiwalled Carbon Nanotubes supported CoSbS (CoSbS/MWCNT) composites are synthesized by a simple hydrothermal technique and are used as an electrocatalyst for the reduction of tri-iodide to iodide ( I 3 − / I − ). The crystalline structure, morphology, and quantum states of the synthesized samples are analyzed. In a series of electrochemical studies, the CoSbS/MWCNT demonstrated superior electroconductivity and electrocatalytic activity over pristine CoSbS. Notably, the Power Conversion Efficiency (PCE) is reached 6.0% with the CoSbS/MWCNT counter electrode, outpacing the corresponding CoSbS (4.4%) and Co9 S8 (1.8%). It is also an effective material for supercapacitors. Moreover, CoSbS/MWCNT has the maximum specific capacity of 382 C g −1 with 3 A g −1 with the acceptable capacitance retention of around 82% over 1000 charge-discharge cycles and excellent rate capability (∼143 C g −1 at 3 A g −1 ). Through these findings, it can be discovered that CoSbS/MWCNT is not only a feasible substitute for the standard Pt counter electrode in DSSCs but also has the capacity to store energy. The excellent conversion and storage performance highlight the potential of CoSbS/MWCNT for a photo-powered energy system.